Bone regeneration using gene-activated matrices - D’Mello, Sheetal (AAPS J, 2016)
Gene delivery to bone is a potential therapeutic strategy for directed, sustained and regulated protein expression. Tissue engineering strategies for bone regeneration include delivery of proteins, genes (viral and non-viral-mediated delivery) and/or cells to the bone defect site. In addition, biomimetic scaffolds and scaffolds incorporating bone anabolic agents greatly enhance the bone repair process. Regional gene therapy has the potential of enhancing bone defect healing and bone regeneration by delivering osteogenic genes locally to the osseous lesions, thereby reducing systemic toxicity and the need for using supraphysiological dosages of therapeutic proteins. By implanting gene-activated matrices (GAMs), sustained gene expression and continuous osteogenic protein production in situ can be achieved in a way that stimulates osteogenesis and bone repair within osseous defects. Critical parameters substantially affecting the therapeutic efficacy of gene therapy include: the choice of osteogenic transgene(s), selection of non-viral or viral vectors, the wound environment, and the selection of ex vivo and in vivo gene delivery strategies, such as GAMs. It is critical for gene therapy applications that clinically beneficial amounts of proteins are synthesized endogenously within and around the lesion in a sustained manner. It is therefore necessary that reliable and reproducible methods of gene delivery be developed and tested for their efficacy and safety before translating into clinical practice. Practical considerations such as the age, gender and systemic health of patients and the nature of the disease process also need to be taken into account in order to personalize the treatments and progress towards developing a clinically applicable gene therapy for healing bone defects. This review discusses tissue engineering strategies to regenerate bone with specific focus on non-viral gene delivery systems.